2017
DOI: 10.1017/jfm.2017.654
|View full text |Cite
|
Sign up to set email alerts
|

A numerical investigation of the asymmetric wake mode of a squareback Ahmed body – effect of a base cavity

Abstract: Numerical simulations of the turbulent flow over the flat backed Ahmed model at Reynolds number $Re\simeq 4\times 10^{5}$ are conducted using a lattice Boltzmann solver to clarify the mean topology of the static symmetry-breaking mode of the wake. It is shown that the recirculation region is occupied by a skewed low pressure torus, whose part closest to the body is responsible for an extra low pressure imprint on the base. Shedding of one-sided vortex loops is also reported, indicating global quasi-periodic dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 56 publications
9
67
0
Order By: Relevance
“…Simulations which accurately capture the wake unsteadiness at high Reynolds number, and which furthermore extend over the large time scales of bi-modal switching, are very costly. Unsteady simulations of simplified bluff body flows have been performed using partially averaged Navier-Stokes (PANS), simulations (Mirzaei, Krajnović & Basara 2015;Rao et al 2018a), unsteady Reynolds-averaged Navier-Stokes simulations (Khalighi, Chen & Iaccarino 2012), detached eddy simulations and large eddy simulations (Krajnović & Davidson 2003;Serre et al 2013;Aljure et al 2014;Östh et al 2014;Rao et al 2018b), some also employing a lattice Boltzmann formulation (Roumeas et al 2009;Lucas et al 2017 The present study achieves what we believe are the first simulations of wake bi-modality, capturing both asymmetric states, for a blunt bluff body. No artificial forcing nor inlet perturbations are applied to trigger bi-modality; the flow develops naturally from a steady inlet velocity condition, with bi-modal switches occurring randomly.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Simulations which accurately capture the wake unsteadiness at high Reynolds number, and which furthermore extend over the large time scales of bi-modal switching, are very costly. Unsteady simulations of simplified bluff body flows have been performed using partially averaged Navier-Stokes (PANS), simulations (Mirzaei, Krajnović & Basara 2015;Rao et al 2018a), unsteady Reynolds-averaged Navier-Stokes simulations (Khalighi, Chen & Iaccarino 2012), detached eddy simulations and large eddy simulations (Krajnović & Davidson 2003;Serre et al 2013;Aljure et al 2014;Östh et al 2014;Rao et al 2018b), some also employing a lattice Boltzmann formulation (Roumeas et al 2009;Lucas et al 2017 The present study achieves what we believe are the first simulations of wake bi-modality, capturing both asymmetric states, for a blunt bluff body. No artificial forcing nor inlet perturbations are applied to trigger bi-modality; the flow develops naturally from a steady inlet velocity condition, with bi-modal switches occurring randomly.…”
mentioning
confidence: 68%
“…For blunt bluff body flows, it is well known that a low-pressure toroidal vortex structure typically appears in the near wake, and can be visualised by considering iso-contours of negative pressure coefficient (Krajnović & Davidson 2003;Roumeas et al 2009;Lucas et al 2017). Figure 9 shows high-frequency snapshots of these pressure iso-contours for the very fine grid simulations of the lorry and the baseline grid simulations of the Ahmed body, respectively exhibiting vertical and horizontal bi-modality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The fact that only one of these two states remains when the data are filtered with either a low-pass filter or a high-pass filter (both with a cut-off frequency of 5 Hz) provides useful information for the implementation of flow control strategies aiming to reduce the drag. It is shown that the selection of an axisymmetric pressure distribution is not a necessary condition to achieve a base drag reduction, although it is the only admissible low-drag scenario when the short-time wake dynamics are filtered-out, for example, by adding a cavity to the model base, as shown by Lucas et al 25 The existence of a link between the "pumping mode" described in the work of Berger et al 5 and the flapping mode isolated at St D ≈ 0.10 by Rigas et al 36 is also proposed. Both modes appear to be associated with the alternate expansion and contraction of the coherent structures forming the "hairpin vortex," with characteristic frequencies ranging from St D = 0.08, close to the centre of the base, up to St D = 0.095 in proximity to the model trailing edge.…”
Section: Discussionmentioning
confidence: 99%
“…Their shedding has been found to be at the origin of the flapping motions of the wake closure that characterises the short-time wake dynamics. 18,25 Additional information on such dynamics can be gathered from the spectral analysis of the signals recorded by pressure taps located at different radial locations. As shown in Fig.…”
Section: Physics Of Fluidsmentioning
confidence: 99%